2019
DOI: 10.1186/s12984-019-0636-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased gait variability during robot-assisted walking is accompanied by increased sensorimotor brain activity in healthy people

Abstract: BackgroundGait disorders are major symptoms of neurological diseases affecting the quality of life. Interventions that restore walking and allow patients to maintain safe and independent mobility are essential. Robot-assisted gait training (RAGT) proved to be a promising treatment for restoring and improving the ability to walk. Due to heterogenuous study designs and fragmentary knowlegde about the neural correlates associated with RAGT and the relation to motor recovery, guidelines for an individually optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 91 publications
1
17
0
Order By: Relevance
“…While this is a possibility, the level of variability is similar to that reported in Koenraadt et al (2014) (n = 11, 10 repetitions/condition) [15]. Further, methodologically the signal-to-noise for this study is likely increased with greater number of trials per condition and larger sample size than some gait studies using fNIRS [16,27,36]. So, it is conceivable that the variability reflects actual individual variation in brain activation associated with robotic exoskeleton assisted gait.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…While this is a possibility, the level of variability is similar to that reported in Koenraadt et al (2014) (n = 11, 10 repetitions/condition) [15]. Further, methodologically the signal-to-noise for this study is likely increased with greater number of trials per condition and larger sample size than some gait studies using fNIRS [16,27,36]. So, it is conceivable that the variability reflects actual individual variation in brain activation associated with robotic exoskeleton assisted gait.…”
Section: Resultssupporting
confidence: 79%
“…In Koenraadt et al 2014, decreased oxyHb is found with normal walking and precision stepping in the SMA [15]. Berger et al 2019 showed decreased oxyHB for treadmill walking over SMA/PMC compared with the sensorimotor cortex [27]. In fMRI research, two studies found increased activation for passive compared with active stepping in prefrontal and posterior parietal area of the precuneus [10], and cingulate and medial frontal areas; motor response inhibition was proposed as a potential mechanism to explain the increased activity for passive stepping [11].…”
Section: Changes In Oxy-and Deoxy-hemoglobin During Robotic Exoskeletmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, uncovering the link between age- and disease-related impairments of motor control and changes in brain activity to identify objective biomarkers for neuroplastic changes and motor recovery is a future goal in neurorehabilitation (Bönstrup et al, 2018 ; Coscia et al, 2019 ). Based on this, individualized training protocols and interventions with new technologies such as BMI and NIBS could be developed, which enable sustainable rehabilitation and optimization of the outcome and effectiveness of motor recovery (Semprini et al, 2018 ; Steinberg et al, 2019 ; Berger et al, 2019a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the brain conditions, several brain signal acquisition techniques are used. For acquiring the brain signal noninvasively, commonly used methods include electroencephalography [10,11], functional near-infrared spectroscopy (fNIRS) [12][13][14], functional magnetic resonance imaging (fMRI) [15], and magnetoencephalography [16][17]. fNIRS is a brain imaging technique that utilizes near-infrared light to detect the cerebral blood ow in the brain.…”
Section: Introductionmentioning
confidence: 99%